2020
DOI: 10.1210/clinem/dgaa090
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Follistatin and Activin A and Their Regulation by Insulin in Obesity and Type 2 Diabetes

Abstract: Background Circulating follistatin (Fst) binds activin A and thereby regulates biological functions such as muscle growth and β-cell survival. However, Fst and activin A’s implication in metabolic regulation is unclear. Objective To investigate circulating Fst and activin A in obesity and type 2 diabetes (T2D) and determine their association with metabolic parameters. Further, to examine regulation of Fst and activin A by ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Previous studies have shown that circulating FST is higher in patients with T2D than in glucose-tolerant individuals or obese individuals and that activin A levels are similar between these groups (Perakakis et al, 2019;Sylow et al, 2020). However, our results indicated that the level of serum FST was lower in patients with diabetic cardiomyopathy than in healthy individuals, and the in vitro experimental results also verified this finding.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that circulating FST is higher in patients with T2D than in glucose-tolerant individuals or obese individuals and that activin A levels are similar between these groups (Perakakis et al, 2019;Sylow et al, 2020). However, our results indicated that the level of serum FST was lower in patients with diabetic cardiomyopathy than in healthy individuals, and the in vitro experimental results also verified this finding.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, although FST correlates with insulin resistance in patients with T2D, the effect of insulin on reducing circulating FST is preserved in obese individuals and patients with T2D. Moreover, with an increasing insulin exposure time, FST mRNA levels in human hepatocytes decrease gradually (Sylow et al, 2020). Therefore, the decline in the level of FST in diabetic cardiomyopathy might be explained by prolonged exposure to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated circulating levels of follistatin are observed in obese patients with T2DM accompanied by insulin resistance. 41 , 88 Follistatin was shown to ameliorate fibrosis and improve kidney function in chronic kidney disease, 89 suggesting its application in disorders accompanied by elevated blood pressure, such as chronic kidney disease, obesity, and T2DM. 90 In our ABN analysis, elevated follistatin plasma levels contribute to hypertension development, which affects ECW levels, and thus indirectly correlates with LBP disability ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Except for ERFE, [137][138][139][140] the circulating levels of IL-6, FGF21, FST, irisin, GDF15, CHI3L1 and ANGPTL4, have been reported to be increased in insulin resistant conditions such as obesity, 33,57,141 T2D, 33,83,84,120,[142][143][144][145][146] polycystic ovary syndrome 147 and non-alcoholic fatty liver disease. 141,148 However, as described, the production and release of these exerkines are also highly induced in response to acute exercise after which insulin sensitivity is enhanced.…”
Section: Exerkines In Metabolic Diseasesmentioning
confidence: 99%